Efforts To Increase Students' Learning Motivation Through Audio-Visual Media - Pasaribu, Muhammad Mizwar; Sormin, Darliana; Lubis, Jumaita Nopriani (Pascasarjana Universitas KH. Abdul Chalim, 2025)
This study aims to enhance students' learning motivation in the subject of Al-Qur'an through the use of audio-visual media. Audio-visual media combine sound (audio) and still or moving images (visual) to deliver information. The type of research used in this study is Classroom Action Research (CAR). CAR is a classroom-based research activity conducted to solve instructional problems faced by teachers, improve the quality and outcomes of learning, and experiment with new teaching methods to enhance the overall learning process. Data collection techniques include observation and documentation. The data analysis techniques involve data reduction, data presentation, drawing conclusions, and formulating findings. The research procedure begins with a pre-cycle phase, followed by Cycle I and Cycle II, ensuring that learning outcomes exceed the set competency criteria, with each cycle consisting of three meetings. The findings of this study indicate that various types of audio-visual media, such as educational videos and animations, were used to present the content of the Al-Qur'an in a more creative and engaging manner. By utilizing a combination of images and sound, the learning process becomes more engaging, interactive, and easier to comprehend. With proper implementation, audio-visual media not only enhance students' motivation to learn but also help them acquire knowledge in a more enjoyable and efficient way.